Nutrient accumulation, export and cycling in Jatropha curcas L . - Carlos Hissao Kurihara; Hamilton Kikuti; Flávio Ferreira da Silva Binotti; Cesar José da Silva (Revista Ceres, 2016)
ABSTRACT The knowledge concerning nutrient accumulation rate allows defining the best amount and most appropriate time for its supply. Estimating nutrient amount in the aerial part of the plants is particularly important to species such as Jatropha curcas L., since there are no consistent calibration studies to indicate the amount of fertilizer to be applied. The objective of this study was to evaluate nutrient accumulation, export and cycling in Jatropha curcas. The experiment was carried out in Cassilândia, state of Mato Grosso do Sul, Brazil, during 52 months in a completely randomized design, with four replications and fifteen treatments, which consisted of different evaluation times. A large variation in the amount of nutrients accumulated in leaves was found due to senescence and leaf abscission in the driest and/or coldest period of the year. Nutrient accumulation in the aerial part is relatively low in the first 22 months. To meet Jatropha curcas requirements, fertilization during the first two years must provide 40; 50; 50; 21; 16; 5; 0.7; 0.3; 4; 8 and 1 kg ha-1 of N, P2O5, K2O, Ca, Mg, S, B, Cu, Fe, Mn and Zn, respectively. From the third year of cultivation, topdressing fertilization should restitute 40, 110, 55 and 3 kg ha-1 of N, P2O5, K2O and S, respectively. To replace the exported amount of nutrients, it should be supplied more 50, 100, 30 and 3 kg ha-1 of N, P2O5, K2O and S, respectively, per ton of grain to be produced.